Stevia rebaudiana extract (main components: chlorogenic acid and its analogues) as a new safe feed additive: evaluation of acute toxicity, sub chronic toxicity, genotoxicity, and teratogenicity - Li, Yuting; Zhu, Liping; He, Dongsheng; Fang, Ling; Li, Yajing; Tang, Shusheng (Frontiers in Veterinary Science, 2025)
IntroductionStevia rebaudiana extract (SREC), primarily composed of chlorogenic acid and its analogues, is a promising feed additive with potential benefits for livestock performance, gut health, and antioxidant capacity. However, its safety evaluation has not been comprehensively studied.MethodsThe safety of SREC was assessed through a series of tests, including acute oral toxicity in mice and rats, a 90-day subchronic toxicity test in rats, genotoxicity assays (Ames test, mouse bone marrow micronucleus test, and mouse sperm abnormality test), and teratogenicity evaluation in pregnant rats.ResultsThe acute oral toxicity test indicated that the LD₅₀ of SREC in mice and rats was greater than 5,000 mg/kg body weight. In the 90-day subchronic toxicity test, SREC was non-toxic at doses up to 50,000 mg/kg in feed. The Ames test showed no mutagenic effects on Salmonella typhimurium strains TA97, TA98, TA100, and TA102. No genotoxicity was observed in the mouse bone marrow micronucleus test or the sperm abnormality test, with no significant differences compared to controls (p > 0.05). Similarly, no teratogenic effects were found in pregnant rats, with normal embryonic development across treatment and control groups.DiscussionSREC exhibited low toxicity in both acute and subchronic tests, and no evidence of genotoxicity or teratogenicity was observed. These findings suggest that SREC is safe as a potential feed additive and provide valuable reference data for its safety evaluation.